Anti-Diarrhea Effects of OGI Produced Using Saccharomyces Boulardii As Starter Culture (International Journal of Scientific Research and Management (IJSRM), 2022)
The antidiarrhea effect of 96 hr fermented ‘Ogi’ (Corn slurry) using Saccharomyces boulardii as starter culture against Escherichia coli was investigated in-vitro and in-vivo using Wistar rats. The pH and titratable acid of the slurry were determined, while the antimicrobial effect on diarrhea causing organisms, Escherichia coli was also determined. Using well diffusion method, 0.1 ml of the slurry effectively inhibited the growth of E. coli with zones of inhibition ranging from 2.4 (±0.14)a mm at 24hr of fermentation to 8.4(±0.11)d mm at 96hr of fermentation. The zones of inhibition increased with increasing period of fermentation of the filtrate which is Ogi. The titratable acidity of the fermenting Guinea corn increased with increasing period of fermentation and reached a peak at 96hr of fermentation (0.25 (± 0.02)c %). The pH however decreased with increase in the period of fermentation from 5.65 (± 0.01)a at 0hr to 3.54 (± 0.02)e at 96hr of fermentation. The antidiarrheal activity of Guinea corn slurry was investigated in-vivo using E. coli to induce diarrhea. The infected test groups of rats were fed orographically with fermented slurry of Guinea corn (Ogi), whereas positive control group was neither being infected nor fed with ogi while negative control group was infected with E. coli but not fed with Ogi. In test groups fed with fermented ‘Ogi’ recovered from diarrhea infection. The obtained results of the present study confirm the possibility of using fermented guinea corn slurry (Ogi) produced using Saccharomyces boulardii as starter culture for the treatment of diarrhea rather than the organisms in drug presentation which reduces compliance in diarrheal patients most especially children.